The Effect of Cabbage and Aloevera Compress on Breast Engorgement in Post Partum Mothers - Doloksaribu, Meli; Barus, Emi Br (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
Swelling of the breast is damming of milk due to narrowing of the lactiferous ducts or by glands that are not completely emptied. Breasts are generally enlarged, hard, and uncomfortable due to increased blood supply to the breasts along with milk production. The purpose of this study was to determine the effect of cabbage and aloe vera compresses on breast swelling in post partum mothers. The sampling technique in this study is accidental sampling. The instrument used was a questionnaire sheet using the Six Point Engagement Scale (SPES). The population and samples in this study were all post partum mothers, 30 people, with 15 cabbage intervention groups and 15 people in the aloe vera intervention group. The research was conducted from January to May 2023. The research analysis used the Paired T-Test. The results of the Paired T-Test the effect of cabbage and aloe vera compresses on breast swelling in postpartum mothers can be seen from the p value of 0.000 (<0.05), it can be concluded that there is an effect of cabbage and aloe vera compresses on breast swelling in postpartum mothers partum. There is an effect of cabbage and aloe vera compresses on breast swelling in post partum mothers.